A trianoni magyar-román államhatár határjeleinek története 1921-25 - Suba, János (Közép-Európai Közlemények, 2009)
Landmarks indicate national boundaries. They are supposed to visualise the frontiers of a country. Neighbouring states have good relations if the extension of the countries is clearly established. Therefore, boundaries are being defined by descriptions, maps and actual landmarks. The types (tergeminate, main, interposed) and forms of the boundary marks (stones) were established by the Hungarian–Roumanian Frontier Commission. On marshy terrain wooden boundary marks were used. Along the 10 sections of the 428 km border-line there were set as much as 3660 boundary marks.